Umbilical hernia and pregnancy. A case presentation. - Julio Sarmiento Sánchez; Lidia Torres Ajá; Doris González Díaz (Medisur, 2008)
A case of a 30 year-old black, female patient, born in Angola, Africa with past history of multiple miscarriages is presented. She stated that the last pregnancy she had had abdominal pain, as well as some other less common discomfort. A great umbilical hernia defect was detected which affected the pregnant uterus and other abdominal viscera. It was necessary to admit the patient into the hospital during the last 10 weeks of pregnancy until the cesarean surgery and the hernia reparation was performed. The mother and infant developed satisfactorily and were discharged from the hospital. They were followed up in consultations to which they never assisted. The low frequency of occurrence of this association which was corroborated by means of national as well as international bibliographical revision. This led us to prepare this report.